Subjective criteria associated with return-to-play in sports physical therapy - Vanessa Kume; Alessandro Haupenthal; Guilherme S. Nunes; Giuliano Mannrich; Daniela dos Santos Haupenthal; Bruna Borges Wageck (Fisioterapia em Movimento)
AbstractIntroduction The Subjective Daily Assessment Scale (ESAD) is based on the visual analog scale (VAS) and assesses six parameters (pain, edema, heat, mobility, sensitivity, and confidence).Objective This study aimed to examine the association between the analyzed variables as assessed by the ESAD and physical therapy clinical discharge and return-to-play of injured athletes.Method Eighty-one patient records of athletes were analyzed; mean sample age was 23.9 ± 6.3 years. The athletes received treatment through the Sports Physical Therapy program of Santa Catarina State University, Brazil, between 2008 and 2011. Six parameters were ranked on a scale from 0 to 10, with 0 being the best possible condition and 10 the worst. Data analysis was conducted using stepwise Cox regression.Results At the time of the injury, the mean score for confidence was 5.82 ± 0.48, and at the time of return-to-play, it was 0.48 ± 1.1; the mean score for pain decreased from 3.7 ± 2.64 to 0.34 ± 0.83. However, due to the strong association between pain and confidence, only confidence remained in the final model. For each reduction in the value reported for confidence, the probability of return-to-play was 0.62 times greater.Conclusion The results showed that confidence was the best variable for predicting athlete return-to-play.